An aggregation/disaggregation approach to obtain robust conclusions with ELECTRE TRI - Dias, Luís (2002)
http://www.sciencedirect.com/science/article/B6VCT-44X69C1-9/1/0ba5b9d678298d943508eeb80bb139da